Ultrasound Assisted Electrodeposition of Cu-SiO2 Composite Coatings: Effect of Particle Surface Chemistry. Issue 8 (1st January 2019) - Bengoa, L. N.; Ispas, A.; Bengoa, J. F.; Bund, A.; Egli, W. A.
Abstract : Electrodeposition of Cu-SiO2 composite coatings from an alkaline non-cyanide electrolyte containing glutamate as complexing agent was studied. Silica mesoporous particles were synthesized using a modified Stöber methodology, and later their surface chemistry was changed by functionalizing them with 3-aminopropyltriethoxysilane. Particles microstructure and morphology were characterized (SEM, TEM, XRD) and their charging behavior in several electrolytes was studied through ζ-potential measurements. Galvanostatic deposition was performed in electrolytes containing both as-prepared and functionalized SiO2 at various current densities, and the influence of ultrasonic irradiation (37 Hz) was evaluated. For some experiments, 1.5 g L − of Polyquaternium 7 were added to the solution. SEM and XRD were used to characterized coatings morphology and microstructure, whereas EDS was used to estimate SiO2  wt%. The results showed that the effect of ultrasound on the codeposition process depends on current density and particle surface chemistry. All the trends observed in this study could be explained taking into account ζ-potential values recorded and previously reported theories. Adjusting the experimental conditions, it was possible to obtain deposits with SiO2 contents of ≈5 wt%. Finally, it was found that both ultrasonic irradiation and Polyquaternium 7 affect the morphology and crystal orientation of the deposits.